Local Community Perceptions and Attitudes Towards Butterflies and Ecotourism in West Sumatera - Hnin Phyu Wai; Henny Herwina; Dahelmi dahelmi; Jasmi Jasmi; Muhammad Nazri Janra (Universitas Andalas, 2023)
One of the most biodiverse nations in the world, Indonesia is home to a wide variety of butterflies as well as other animals and plants. Butterflies play a significant role in the ecosystem, both in the pollination process and in the process of detecting environmental changes in the ecosystem. One alternate strategy for preserving biodiversity and natural resources while boosting a nation's economy is ecotourism. This study aims to investigate the perceptions and attitudes of local communities in West Sumatera regarding with butterflies and ecotourism. The study was conducted from February to March, 2023 by using two-page questionnaire developed to collect social information regarding with ecotourism and butterflies through in-depth interview with respondents who was currently living in West Sumatra. A total of 30 respondents (15 Male, 15 female) from various background were questioned. According to the survey’s findings, the majority of the population (93%) was passionate about protecting biodiversity and has extensive understanding of ecotourism and butterflies. Additionally, the majority of respondents (93%) mentioned that they would love to join Butterfly Watching Program. The respondents indicated that West Sumatera has a lot of ecotourism destinations. To draw visitors, a more sophisticated ecotourism program centered on beautiful wildlife and flora should be established.